A MULTICENTRIC STUDY ON BREAST CANCER IN ULTRA YOUNG WOMEN: III – THERAPEUTIC ASPECTS AND ONCOLOGICAL OUTCOMES - Yoshimura, Adriana Akemi; Mattar, André; Mota, Bruna S.; Fristachi, Carlos Elias; Pessoa, Eduardo Carvalho; Andrade, Felipe Eduardo; Tosello, Giuliano; Vespoli, Heloísa Maria De Luca; Oliveira Junior, Idam de; Borges, João Bosco Ramos; et al. (Mastology, 2021)
Introduction: We have originally introduced the concept of ultra young women (UYW), defined as age ≤ 30 years old. It is generally accepted that UYW patients with breast cancer (BC) share some unfavorable outcomes and the patients are faced with family and professional problems, and unique quality of life issues, including loss of fertility, contraception, pregnancy, sexuality, cancer during pregnancy, body image and emotional distress, that complicate treatment decisions making. Objectives: Study the type of surgical and systemic treatment and oncologic outcomes in UYW with BC. Methods: We conducted a multicentric, observational, retrospective study of consecutive BC UYW patients. Only patients with infiltrating BC were included. Nine Mastology Centers located in the State of São Paulo participated. The following data were recorded: type of surgery, chemotherapy, endocrinetherapy, and radiotherapy. Individual oncologic evolution was analyzed and the patients were classified as alive without disease (AWD), alive with local recurrence (ALR), alive with systemic recurrence (ASR), died from BC (DBC) or died from another cause (DOC). The research protocol was approved by the Ethics Committee of all Collaborative Centers. Results: Sixteen percent of UYW with BC underwent mastectomies, 10% nipple-sparing mastectomies and 16% breast conservative surgeries. About 50% had immediated breast reconstruction. Sentinel node biopsy was performed in 24%. 18% had more than four compromised LNs, 8% with extracapsular leak. 37% received adjuvant or palliative chemotherapy. 61% were submitted to irradiation. 54% had adjuvant hormonetherapy. The mean time of follow-up was 41.5 months (1.5-207). It was observed that 59% were AWD, 1% ALR, 7% ASR and 23% DBC, unfortunately standing out the elevated contingent of BC-related deaths. Conclusions : BC therapy in UYW were tailored according to individual characteristics, but the oncological outcomes in this age range at the moment could be considered unfavorable.